Pengaturan Kecepatan Motor Induksi 3 Fasa Dengan Metode V/F Konstan Dan Kontrol PID-CHR - Maulana Malik Ibrahim (Sekolah Tinggi Teknik PLN, 2022)
Its sturdy construction and simple maintenance make the induction motor the main driving machine in the industry. Induction motor speed setting is one of the operating conditions that are often used so that an inverter 3 phase is needed as an induction motor speed regulator. Inverter 3 phase is a device used to make AC voltage 3 phase from dc voltage supply source. Inverter 3 phase used type Current Source Inverter that uses the Sinusoidal Pulse Width Modulation (SPWM) method with constant voltage / frequency control (v / f constant). In optimizing the motor response, it is used to control feedback with a low error rate, pid-CHR control is applied which can cover a wider range of operating conditions and is easily adjustable.